THE ROLE OF THE LEGAL SECTION OF THE CITY POLICE DEPARTMENT AND THE LEGAL DIVISION OF THE REGIONAL POLICE DEPARTMENT IN ASSISTING WITH DISCIPLINARY CODE OF ETHICS VIOLATIONS AND CRIMINAL ACTS BY POLICE OFFICERS IN BENGKULU - Sonya Renanthanda Niagara; Agusalim; Herlambang (Universitas Bengkulu, 2025)
The issue examined in this thesis is the role of the legal section of the city police department and the legal division of the regional police department in assisting police officers who commit disciplinary violations, ethical code breaches, and criminal acts, as well as the challenges faced by these legal sections in providing such assistance. The research method used is empirical legal research, also known as field research, which examines the applicable legal provisions and what occurs in reality within society. The findings indicate that the Legal Section of the City Police Department and the Legal Division of the Regional Police Department play a crucial role in supporting police officers who commit disciplinary violations, ethical breaches, and criminal acts. This support, provided based on orders from the heads of the city and regional police departments, ensures that the rights of problematic police officers are not neglected. In practice, the legal sections have been quite effective in providing legal assistance, despite facing various internal and external challenges in fulfilling their roles. Keywords: Legal Assistance, Disciplinary Violations, Code of Ethics, and Criminal Acts